Microbiome-Informed Dosing: Exploring Gut Microbial Communities Impact on Mycophenolate Enterohepatic Circulation and Therapeutic Target Achievement - Saqr, Abdelrahman; Cheng, Shen; Al-Kofahi, Mahmoud; Staley, Christopher; Jacobson, Pamala A (Clinical pharmacology and therapeutics, 2025)
Pharmacomicrobiomics is an emerging field due to important microbiome effects on pharmacokinetics and clinical outcomes. However, the application of this knowledge remains limited. Mycophenolic acid (MPA) is the primary active metabolite of the immunosuppressant, mycophenolate mofetil (MMF). MPA undergoes glucuronidation to form MPA glucuronide (MPAG) which is deglucuronidated by bacterial β-glucuronidases and reformed as MPA through enterohepatic circulation (EHC). We studied the stool microbiome effect on the pharmacokinetics of MPA, its metabolites, and EHC in hematopoietic cell transplant (HCT) recipients using a semi-mechanistic population pharmacokinetic model. Microbiome communities were identified using correlation network analysis, and their impact on pharmacokinetics was assessed using full fixed-effects modeling. Simulations were then conducted to evaluate MMF dosing regimens and to assess the impact of community abundance on EHC and MPA therapeutic target achievement. High abundance of Bacteroides uniformis-dominant and Bacteroides vulgatus-dominant communities was associated with higher EHC and an increase in MPA exposure. Low abundance of these communities was associated with a 52-80% and 4-83% lower EHC and MPA exposure, respectively. Simulations showed 70% of individuals with low abundance of these communities achieved the therapeutic target at the typical HCT MMF dose of 1,000 mg Q8 hours IV; however, ≥ 95% were within the therapeutic target at 1,250 mg Q8 hours or 1,750 mg Q12 hours. EHC accounted for 34% of the MPA area under the curve. Elimination of EHC reduced troughs by 100%. This work quantifies the microbiome's effect on pharmacokinetics, paving the way for future microbiome-informed dosing to optimize therapeutic target attainment.